The Attributes of School Leaders in a Time of Crisis: An Exploratory Case Study of the COVID-19 Pandemic in Saudi Arabia - Alomair, Latifah (2021)
The Coronavirus pandemic is a crisis that has fundamentally changed the fabric of school leadership globally. School leaders are required to work to mitigate the effects of this crisis through their demonstration of effective leadership attributes. Currently, a few western studies highlight the attributes of school leader’s desirable in a time of disruption, but their findings have little relevance to middle-eastern contexts. This study addresses such gap by focusing on the exploration of leadership attributes of Saudi Arabian school leaders demonstrated during the COVID-19 pandemic. It focuses on the importance of human leadership as a part of school crisis leadership. Using an exploratory case study approach, a qualitative open-ended questionnaire was administered to a sample of Saudi Arabian school principals to explore their school leadership attributes exercised during the crisis. It was found that the circumstances imposed by the pandemic had a strong influence on their leadership attributes and their responses to the crisis. Nine leadership attributes found that leaders have: become more eager for development, learnt to remain calm, endured stress and difficulties, become more compassionate, supportive, strategic, emotionally intelligent, intuitive and better communicators. They found that these attributes helped them succeed in managing the crisis by better understanding micro and macro aspects of their schools. The findings highlight leadership qualities required for stronger school leadership within Saudi Arabian schools during periods of rapid change, and may benefit those involved in school leadership development and principal preparation in Middle-eastern contexts.